Quantifying aluminum and semiconductor industry perfluorocarbon emissions from atmospheric measurements. Issue 13 (10th July 2014) - Kim, Jooil; Fraser, Paul J.; Li, Shanlan; Mühle, Jens; Ganesan, Anita L.; Krummel, Paul B.; Steele, L. Paul; Park, Sunyoung; Kim, Seung‐Kyu; Park, Mi‐Kyung; Arnold, Tim; Harth, Christina M.; et al.
Abstract The potent anthropogenic perfluorocarbon greenhouse gases tetrafluoromethane (CF4) and hexafluoroethane (C2F6) are emitted to the atmosphere mainly by the aluminum and semiconductor industries. Global emissions of these perfluorocarbons (PFCs) calculated from atmospheric measurements are significantly greater than expected from reported national and industry‐based emission inventories. In this study, in situ measurements of the two PFCs in the Advanced Global Atmospheric Gases Experiment network are used to show that their emission ratio varies according to the relative regional presence of these two industries, providing an industry‐specific emission "signature" to apportion the observed emissions. Our results suggest that underestimated emissions from the global semiconductor industry during 1990–2010, as well as from China's aluminum industry after 2002, account for the observed differences between emissions based on atmospheric measurements and on inventories. These differences are significant despite the large uncertainties in emissions based on the methodologies used by these industries.